Presenting the management model of sports talents of Iranian students based on data foundation theory - Mahsa Mortezaeian; Zahra Sadat Mirzazadeh; Mohammad Keshtidar; Mahdi Talebpour (Islamic Azad university, Isfahan Branch, 2022)
Objective: The purpose of this research was to present a model of sports talent management of Iranian students based on grounded theory.Methodology: In this research, the grounded theory method was utilized to theorize the topic based on a series of data coding steps using MAXQDA software, which ultimately resulted in the identification of the final list of key factors to present a model of sports talent management of Iranian students. The participants of this study consisted of sports management professors and experts with rich experiences in the field of sports talent management. The sampling method was purposeful with professors and experts in the field of sports talent management and it was used up until theoretical saturation. Therefore, 16 experts in this field were interviewed.Results: After familiarizing and mastering the data, initial coding was carried out. In the second stage, after refining the initial codes, we came up with 28 concepts. The final categories were counted after categorizing 9 categories, and the way they are used is included in the model. This model considered leadership and management of sports talent, the growth and excellence of human force, the design of the system for monitoring, evaluation, and the provision of space, equipment and technology as causal conditions. An intervening condition in this model was talent motivation management. The model also included two categories of expanding the talent identification discourse and regulating interactions with institutions and families as background conditions. Talent identification, talent cultivation and talent management are also assumed as the main strategies in this model. Finally, as is also assumed in the last section, the result of this model should increase the vitality and hope for the future in students.Conclusion: It is expected that the senior officials of the Ministry of Education would implement a model of sports talent management of students at the country level to provide efficient and effective human resources for the future of the Iran's sports.